The Effect of Giving Vermicompos Fertilizer and NPK 16:16:16 on Growth and Production of Edamame Soyabean (Glycine Max (L) Merrill) - Fathiah Rahmadani; Siti Zahrah; Sulhaswardi; Sri Mulyani (Journal of Soilscape and Agriculture, 2023)
This research has been done in the experimental farm of the Faculty of Agriculture, Islamic University of Riau, Jalan Kaharuddin Nasution, Bukit Raya, Pekanbaru. This study take three months since July to September 2019. The objective of this study was to find out the interaction effect and main effect of giving vermi compost fertilizer andNPK 16:16:16 to the growth and production of edamame soybean. The experimental design used was Completely Randomized Design factorial. The first factor was giving vermi compost (V) fertilizer with doses 0, 500, 1000, 1500 g per plot, and second factor was gift NPK 16:16:16 (N) Fertilizer with a dose of 0, 15, 30, 45 g per plot so that there are 16 combinations repeated 3 times to obtain 48 experimental units. Parameters that were observed, were plant height, relative growth rate, number of pods per plant, percentage of fruitful pods, and seed weight per plant. The data analysis of observation in variance then done with test carry on HSD level of 5%. The results showed that the interaction of vermi compost fertilizer and NPK 16:16:16 applications significantly affected the height of the plant, amount of pod per plant, percentage of pod pithy,    and Seed Weight per plant. The best treatment was vermi compost fertilizer at a dose of 1500 g/plot and NPK 16:16:16 with a dose of 30 g/plot (V3N2). The main effect of the application of vermi compost fertilizer was significant to whole parameter. The best treatment was vermi compost with a dose of 1500 g/plot (V3). The main effect  of  application of  NPK 16:16:16 was significant to whole parameter. The the best treatment was NPK 16:16:16 with a dose of 30 g/plot (N2).